Аналіз розвитку акцизного оподаткування в Україні - Сергієнко, Валерія Сергіївна; Фітільова, Вікторія Вікторівна; Коптєва (Фадєєва), Ганна Миколаївна (НТУ "ХПІ", 2017)
Проаналізовано основні тенденції розвитку акцизного оподаткування в Україні. Порівняно ставки акцизного податку на окремі види алкогольних напоїв в Україні та країнах – членах ЄС, здійснено аналіз динаміки зростання ставок акцизу на спирт етиловий в Україні. Проаналізовано фіскальну значимість акцизного оподаткування в Україні. Розглянуто напрями подальшого розвитку акцизного оподаткування в Україні.

The main trends in the development of excise taxation in Ukraine are analyzed. A comparative analysis of excise tax rates for certain types of alcoholic beverages in Ukraine and EU countries has been carried out, and the dynamics of the growth of excise rates for ethyl alcohol in Ukraine has been analyzed. The relationship between consumption volumes and the size of excise rates for alcohol is defined. The fiscal importance of excise taxation in Ukraine in 1998–2017 is analyzed. It is det ermined that for the Ukrainian economy during the development of crisis phenomena, the fiscal significance of the excise tax is characterized. The directions of the further development of excise taxation in Ukraine are considered.
Analysis of the development of excise taxation in Ukraine
Keywords: акцизний податок; адвалорний акциз; специфічний акциз; мінімальний акцизний податок; акцизне навантаження; тютюнові вироби; алкогольні вироби; excise tax; ad valorem excise tax; specific excise tax; minimum excise tax; excise burden